The influence of safety knowledge and safety management practices on safety performance with safety motivation as a mediating variable study at PT. Shinko Plantech - SP Tambunan, Galuh; Ramdansyah, Agus David; Kambara, Roni (Institute of Computer Science (IOCS), 2025)
This study investigates the influence of safety knowledge and safety management practices on safety performance, with safety motivation as a mediating variable, at PT. Shinko Plantech. The research aims to understand how workers’ awareness and implementation of safety procedures contribute to overall safety outcomes in the workplace, and to what extent motivation affects this relationship. A quantitative approach was employed using a survey method. Data were collected from 120 employees through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The findings reveal that both safety knowledge and safety management practices have a significant positive effect on safety performance. Furthermore, safety motivation was found to mediate the relationship between the independent variables (safety knowledge and safety management practices) and the dependent variable (safety performance). These results highlight the critical role of fostering not only strong safety practices and knowledge but also enhancing employee motivation to achieve optimal safety performance. The study contributes to occupational safety literature and provides practical implications for improving safety standards in industrial settings.